1997
DOI: 10.1084/jem.186.7.1015
|View full text |Cite
|
Sign up to set email alerts
|

Required Early Complement Activation in Contact Sensitivity with Generation of Local C5-dependent Chemotactic Activity, and Late T Cell Interferon γ: A Possible Initiating Role of B Cells

Abstract: Complement (C) is an important component of innate immunity, and was also shown recently to participate in induction of acquired B cell humoral immunity. In this study, we present evidence that C also participates in acquired T cell immunity.We found that C was involved in early events of the efferent elicitation phase of contact sensitivity (CS), and delayed-type hypersensitivity (DTH). Thus, CS and DTH were inhibited by administration of a C-blocker, soluble recombinant C receptor-1 (sCR1), when given 30 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
105
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(115 citation statements)
references
References 53 publications
9
105
1
Order By: Relevance
“…Tsuji et al (44) have shown that C5 is required early for the elicitation phase of contact sensitivity and delayed-type hypersensitivity. C5 was required for macrophage chemotactic activity and the late production of IFN-␥.…”
Section: Discussionmentioning
confidence: 99%
“…Tsuji et al (44) have shown that C5 is required early for the elicitation phase of contact sensitivity and delayed-type hypersensitivity. C5 was required for macrophage chemotactic activity and the late production of IFN-␥.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mammalian complement regulatory proteins have also been shown to limit accumulation of leukocytes at sites of inflammation. For instance, administering soluble complement receptor 1 (sCR1) to mice has been shown to limit T cell-mediated delayed-type hypersensitivity responses in skin by limiting the influx of T cells to the site of antigen challenge (53,54). Recent efforts to better define the antiviral functions of Abs during poxvirus infection have revealed an important role for complement in Ab-mediated protection (2, 3).…”
Section: Discussionmentioning
confidence: 99%
“…CD5 + B cells are rare in adults, but they are the predominant B cell population in the fetus, in which they appear to constitute a rather primitive but effective first line of defence against foreign antigens [23]. These cells are characterized by the production of low-affinity immunoglobulin M (IgM) with RF activity, arise early in ontogeny and are considered to represent the bridge linking the innate and acquired immune responses [24]. The production of circulating autoantibodies coupled with their increased frequency in rheumatoid arthritis and Sjögren's syndrome has implicated them in the development of autoimmune diseases [25,26].…”
Section: Introductionmentioning
confidence: 99%